A Compartmented Flow Microreactor System for Automated Optimization of Bioprocesses Applying Immobilized Enzymes - Heinzler, Raphael; Hübner, Jonas; Fischöder, Thomas; Elling, Lothar; Franzreb, Matthias (Frontiers in Bioengineering and Biotechnology, 2018)
In the course of their development, industrial biocatalysis processes have to be optimized in small-scale, e. g., within microfluidic bioreactors. Recently, we introduced a novel microfluidic reactor device, which can handle defined reaction compartments of up to 250 μL in combination with magnetic micro carriers. By transferring the magnetic carriers between subsequent compartments of differing compositions, small scale synthesis, and bioanalytical assays can be conducted. In the current work, this device is modified and extended to broaden its application range to the screening and optimization of bioprocesses applying immobilized enzymes. Besides scaling the maximum compartment volume up to 3 mL, a temperature control module, as well as a focused infrared spot were integrated. By adjusting the pump rate, compartment volumes can be accurately dosed with an error <5% and adjusted to the requested temperature within less than a minute. For demonstration of bioprocess parameter optimization within such compartments, the influence of pH, temperature, substrate concentration, and enzyme carrier loading was automatically screened for the case of transferring UDP-Gal onto N-acetylglucosamine linked to a tert-butyloxycarbonyl protected amino group using immobilized β1,4-galactosyltransferase-1. In addition, multiple recycling of the enzyme carriers and the use of increased compartment volumes also allows the simple production of preparative amounts of reaction products.